2016
DOI: 10.1016/j.geothermics.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Regional crustal-scale structures as conduits for deep geothermal upflow

Abstract: a b s t r a c tGeothermal fluids produced from two of the largest production geothermal fields in the Great Basin have helium isotope ratios that are anomalously high relative to basin-wide trends. These data indicate that the geothermal systems, Dixie Valley, Nevada and McGinness Hills, Nevada have an anomalously high fraction of mantle derived fluid. These connections to deeply derived fluid and heat may supplement crustal heat production and be responsible, in part, for the anomalously high production capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 75 publications
(147 reference statements)
1
7
0
Order By: Relevance
“…Eraifej (2006) measured high 3 He/ 4 He ratios of samples collected from wells and springs along the DST and close to the eastern part of the DSB. Anomalously high 3 He/ 4 He in geothermal fluids indicate that these geothermal systems are associated with more rapid upwelling of mantle derived fluids (Siler & Kennedy 2016). More recently, Schaeffer & Sass (2014) investigated thermal water samples from the eastern side of the Dead Sea valley and suggested that the high geothermal gradient could be best explained if water of deep origin invaded the hydrothermal system of the DSB.…”
Section: Discussion O F T H E 2 -D E L E C T R I C a L C O Nmentioning
confidence: 99%
“…Eraifej (2006) measured high 3 He/ 4 He ratios of samples collected from wells and springs along the DST and close to the eastern part of the DSB. Anomalously high 3 He/ 4 He in geothermal fluids indicate that these geothermal systems are associated with more rapid upwelling of mantle derived fluids (Siler & Kennedy 2016). More recently, Schaeffer & Sass (2014) investigated thermal water samples from the eastern side of the Dead Sea valley and suggested that the high geothermal gradient could be best explained if water of deep origin invaded the hydrothermal system of the DSB.…”
Section: Discussion O F T H E 2 -D E L E C T R I C a L C O Nmentioning
confidence: 99%
“…It is interpreted as underplating because of likely temperatures and oxidation state, and because existing seismic studies (COCORP, PASSCAL) resolved VP attenuation, high VP underplate and high reflectivity there (Catchings and Mooney, 1991;Wannamaker et al, 2007;2008). Mantle sourced 3 He anomalies corroborate this (Kennedy and van Soest, 2007;Siler and Kennedy, 2016), and the situation fits into the general deep hydrological/magmatic paradigm of Crossey and Karlstrom (2012) (Figure 1). An important factor in bringing exploitable fluids surfaceward at Dixie Valley is the intersection of N-S and NE-SW fault trends (Faulds et al, 2011), also resolved in 3D MT surveying (Wannamaker et al, 2013).…”
Section: Technical Approach and Objectivesmentioning
confidence: 56%
“…R/Ra values ranged from 0.35-0.49 in 36-10 fluids to 0.41-0.57 in 28-10 fluids. While these do not rival the high magmatic values seen at Coso or some Cascades volcanoes, they are significantly above the Great Basin background value of ~0.1 van Soest, 2006, 2007;Siler and Kennedy, 2016), signifying that, like the van Soest, 2006, 2007). However, this amount may differ from the long term average depending upon deformation and seismicity, as exemplified in the Mammoth Hot Springs district (Sorey et al, 1998).…”
Section: Production Fluids and Soil Gas Geochemistrymentioning
confidence: 70%
See 1 more Smart Citation
“…Hydrogeologists and geologists want to understand the nature, origin, and role of fluids in such fundamental geological processes as hydrothermal systems [3], deep geothermal systems [4,5], ore deposition [6,7], hydrocarbon maturation, migration and entrapment [8], seismicity [9], and metamorphism [10][11][12]. In sedimentary rocks, fluid pathways include connected rock porosity and lithological changes.…”
Section: Introductionmentioning
confidence: 99%